2013
DOI: 10.4236/ars.2013.21001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of Forest Cover Change and Above-Ground Carbon Stock in Pugu and Kazimzumbwi Forest Reserves, Tanzania

Abstract: A study was conducted to estimate the forest cover change, quantify and map tree above-ground carbon stock using Remote sensing and GIS techniques together with forest inventory. Landsat images of 1980, 1995 and 2010 acquired during dry season were used in the estimation of cover changes. Supervised image classification using Maximum Likelihood Classifier was performed in ERDAS Imagine software to analyze the images and further analysis was performed in Arc GIS 9.3 software. Stratified sampling procedure was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…The results from classification accuracy assessment revealed that the overall accuracy of classification for Itigi thicket was 81%. According to [24] the overall accuracy is acceptable if it is greater than 80%.…”
Section: Itigi Thicket Land Covers Maps and Their Changesmentioning
confidence: 99%
“…The results from classification accuracy assessment revealed that the overall accuracy of classification for Itigi thicket was 81%. According to [24] the overall accuracy is acceptable if it is greater than 80%.…”
Section: Itigi Thicket Land Covers Maps and Their Changesmentioning
confidence: 99%
“…For example, deforestation was reported by Su et al (2011) to be a common phenomenon in Quezon Province, equal to 945 ha were lost due to deforestation during the first year of the project implementation (Mori, 2013). Findings by Kashaigili et al (2013) in Tanzania revealed that during the period 1980-1995 and 1995-2010, closed forest decreased by 635.5 ha (−11.9%) and 1674.9 ha (−31.3%), respectively. Similarly, in the period 1980-1995, settlement and other land uses increased by 85 ha (1.6%) and 439.2 ha (8.2%) between 1995 and 2010.…”
Section: Extent Of Deforestation and Forest Degradationmentioning
confidence: 99%
“…It is apparent that some of the adaptive strategies such as charcoaling are not sustainable and can lead to other multiple effects on the environment and contribute to climate variability and change. A study by Kashaigili et al [8] revealed that for the periods 1980-1995 and 1995-2010, closed forest cover in Pugu Forest Reserve decreased by 4.5% and 25.3% respectively, while for Kazimzumbwi Forest Reserve, the closed forest cover decreased by 11.9% and 31.3% respectively. Among the key drivers for the changes is the charcoal business [9].…”
Section: Coping and Adaptation Strategies By The Coastal Forest Depenmentioning
confidence: 99%